Prevalence and clinical characteristics of the dense fine speckled pattern: Indirect immunofluorescence‐antinuclear antibody screening in the Chinese population. (23rd November 2022) - Meng, Jingjing; Wang, Rong; Luo, Yueming; Li, Siting; Bai, Yina; Song, Ning; Li, Mengtao; Zeng, Xiaofeng; Hu, Chaojun
Abstract: To investigate the prevalence and clinical significance of the dense fine speckled (DFS) pattern in a large‐scale cohort of Chinese patients. Data on the antinuclear antibody (ANA) and extractable nuclear antigen (ENA) autoantibody obtained from 165 498 patients who attended Peking Union Medical College Hospital from January 2019 to December 2021 were retrospectively analysed. The prevalence of the DFS pattern was 1.14%, and it mainly appeared in young patients (≤24 years old). A higher positive rate of the DFS pattern was observed in patients with dermatosis (18.12%) and systemic autoimmune rheumatic diseases (SARDs) (13.53%). The DFS pattern titre was mostly low or medium (≤1:160). A higher titre was associated with an increased risk of SARDs ( p < .001), dermatosis ( p = .015) and pulmonary disease ( p = .016). In 37 patients with ENA autoantibody positivity, anti‐SSA antibody was the most common (2.55%). If the low titre (<1:160) or the DFS pattern with negative ENA autoantibody were to be used as exclusion criteria for SARDs, the diagnosis would have been missed in 42 or 77 patients, respectively. The prevalence of the DFS pattern was low in ANA test samples and was more common in patients with dermatosis and SARDs, but the titre was usually higher in patients with SARDs. There was no evidence that the DFS pattern could be used as an exclusion criterion for SARDs diagnosis. The DFS pattern was associated with certain pathological states, which may inform the clinical significance of the DFS pattern.